Different leafy vegetable cropping systems regulate growth, photosynthesis, and PSII functioning in mono-cropped eggplant by altering chemical properties and upregulating the antioxidant system - Ghani, Muhammad Imran; Ali, Ahmad; Atif, Muhammad Jawaad; Ali, Muhammad; Ahanger, Mohammad Abass; Chen, Xiaoyulong; Cheng, Zhihui (Frontiers in Plant Science, 2023)
Continuous cropping of eggplant threatened regional ecological sustainability by facilitating replanting problems under mono-cropping conditions. Therefore, alternative agronomic and management practices are required to improve crop productivity at low environmental cost for the development of sustainable agricultural systems in different regions. This study examined changes in soil chemical properties, eggplant photosynthesis, and antioxidant functioning in five different vegetable cropping systems over 2-year period., 2017 and 2018. The results showed that welsh onion-eggplant (WOE), celery-eggplant (CE), non-heading Chinese cabbage-eggplant (NCCE) and Leafy lettuce-eggplant (LLE) rotation systems significantly impacted growth, biomass accumulation and yield than fallow-eggplant (FE). In addition, various leafy vegetable cropping systems, WOE, CE, NCCE, and LLT induced significant increases in soil organic matter (SOM), available nutrients (N, P, and K), and eggplant growth by affecting the photosynthesis and related gas exchange parameters with much evident effect due to CE and NCCE. Moreover, eggplant raised with different leafy vegetables rotation systems showed higher activity of antioxidant enzymes, resulting in lower accumulation of hydrogen peroxide, and hence reduced oxidative damage to membranes. In addition, fresh and dry plant biomass was significantly increased due to crop rotation with leafy vegetables. Therefore, we concluded that leafy vegetable crop rotation is a beneficial management practice to improve the growth and yield of eggplant.